2012
DOI: 10.1111/head.12030
|View full text |Cite
|
Sign up to set email alerts
|

Higher Glutamate to Glutamine Ratios in Occipital Regions in Women With Migraine During the Interictal State

Abstract: These findings are consistent with glutamatergic differences in migraine patients during the interictal period compared with healthy controls. We hypothesize that an increased Glu/Gln ratio could arise from neuronal-glial coupling of glutamatergic metabolism differences or an increased neuron/astrocyte ratio in the OC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
42
3
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 47 publications
2
42
3
2
Order By: Relevance
“…Glutamate and glutamine are important in neurotransmission and energy metabolism. In this study, a more elevated Glu/Gln ratio was found in the brains of migraineurs during the pain‐free interval, which the authors suggest could facilitate CSD in the occipital lobe of migraineurs . They caution the study is limited by a small sample size (27 migraineurs and 19 controls), but that a statistical difference in the Glu/Gln ratio between groups was detected .…”
mentioning
confidence: 58%
See 3 more Smart Citations
“…Glutamate and glutamine are important in neurotransmission and energy metabolism. In this study, a more elevated Glu/Gln ratio was found in the brains of migraineurs during the pain‐free interval, which the authors suggest could facilitate CSD in the occipital lobe of migraineurs . They caution the study is limited by a small sample size (27 migraineurs and 19 controls), but that a statistical difference in the Glu/Gln ratio between groups was detected .…”
mentioning
confidence: 58%
“…In this study, a more elevated Glu/Gln ratio was found in the brains of migraineurs during the pain-free interval, which the authors suggest could facilitate CSD in the occipital lobe of migraineurs. 25 They caution the study is limited by a small sample size (27 migraineurs and 19 controls), but that a statistical difference in the Glu/Gln ratio between groups was detected. 25 Although linkage with a known genetic disorder has not been established, low function of glutamate in neurons is associated with schizophrenia, [19][20][21] and some neurological disorders are accompanied by the appearance of antibodies or autoantigen activity to glutamate receptor subunits (eg, GluR3 in Rasmussen's encephalitis).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…During the attack increased levels of glutamate were found in the cerebrospinal fluid of migraine patients [97]. Proton magnetic resonance spectroscopy revealed that a higher glutamate/glutamine ratio is present in migrainous women during the interictal phase compared to controls in the occipital cortex [100], supporting the presence of altered GLU metabolism in migraine.…”
Section: Cortical Hyperexcitability In Migrainementioning
confidence: 84%